Controlling Emitting Dipole Orientation with Methyl Substituents on Main Ligand of Iridium Complexes for Highly Efficient Phosphorescent Organic Light‐Emitting Diodes. Issue 9 (21st April 2015) - Kim, Kwon‐Hyeon; Ma, Jae‐Yeol; Moon, Chang‐Ki; Lee, Jeong‐Hwan; Baek, Jang Yeol; Kim, Yun‐Hi; Kim, Jang‐Joo
<x xml:space="preserve">Abstract</x> Orientation of emission dipoles of heteroleptic iridium complexes in an emitting layer is controlled toward the horizontal direction by substituting the hydrogen atoms of the cyclometalated ligand by methyl groups and demonstrates an organic light‐emitting diode with an unprecedentedly high external quantum efficiency of 34.1% and power efficiency of 157.6 lm W−1 using a new green emitter.